2018
DOI: 10.1186/s12879-018-3149-y
|View full text |Cite
|
Sign up to set email alerts
|

Infection with high proportion of multidrug-resistant bacteria in conflict-related injuries is associated with poor outcomes and excess resource consumption: a cohort study of Syrian patients treated in Jordan

Abstract: BackgroundArmed conflicts are a major contributor to injury and death globally. Conflict-related injuries are associated with a high risk of wound infection, but it is unknown to what extent infection directly relates to sustainment of life and restoration of function. The aim of this study was to investigate the outcome and resource consumption among civilians receiving acute surgical treatment due to conflict-related injuries. Patients with and without wound infections were compared.MethodsWe performed a coh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
46
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
2
2

Relationship

2
6

Authors

Journals

citations
Cited by 58 publications
(51 citation statements)
references
References 26 publications
(28 reference statements)
5
46
0
Order By: Relevance
“…The cohort studies included in the review (52,131,161) showed overall lower risk of bias compared to other study designs.…”
Section: Appraisal Of Risk Of Biasmentioning
confidence: 97%
“…The cohort studies included in the review (52,131,161) showed overall lower risk of bias compared to other study designs.…”
Section: Appraisal Of Risk Of Biasmentioning
confidence: 97%
“…4 Clinical management of conflict-related extremity wounds is challenging, requiring substantial resources, and it is often complicated by infection. [5][6][7] Wound complications can result in prolonged treatment times and increased risk of morbidity and mortality.…”
Section: Introductionmentioning
confidence: 99%
“…The study design was clearly stated in 29 out of the 132 articles included ( Only one study reported sample size calculation and employed representative population although not powered for the prevalence detected nor for the comparison between the sub-groups performed (95). Measures of sampling variation in the results were reported by only four studies (95,161,165,168).…”
Section: Assessment Of Risk Of Biasmentioning
confidence: 99%
“…Only three studies described the use of multivariate analysis -usually logistic regressionto control for confounding (45,147,168). None of the studies took missing data into account in the analysis nor in the discussion, and similarly limitations and potential sources of bias were never mentioned in the discussion, with the exception of one surveillance study performed in Lebanon The cohort studies included in the review (52,131,161) showed overall lower risk of bias compared to other study designs. Two out of the three studies (52,131) lacked detailed description of the statistical methods employed, in particular if and how control for confounding was performed and how losses to follow up were dealt with.…”
Section: Assessment Of Risk Of Biasmentioning
confidence: 99%
See 1 more Smart Citation